Clinical characteristics of patients with sepsis in a pediatric intensive care unit of a second level hospital. - Abreu Pérez, Daysi; Ortega Suárez, Lídice; Montero Álvarez, Lourdes; Lacerda Gallardo , Angel Jesús; Morales Suárez, Irma Guadalupe; Espinosa Domínguez , Madelaine (Medicina Clínica y Social, 2022)
Introduction: In recent years, both morbidity and mortality from sepsis have increased gradually. Objective: To characterize clinical variables of patients with sepsis admitted to a pediatric intensive care unit of the Morón hospital. Material and method: A prospective descriptive study was carried out of pediatric patients admitted to the Intensive Care Unit for Sepsis in the period from January 2015 to December 2018. The universe consisted of 298 children and the sample of 113, of whom they are distributed in different variables. Results: Ages between 2 and 5 years old predominate with 36 patients (31.9%) and female sex in 63 cases (55.7%). In the distribution of the stages at diagnosis, sepsis predominated with 53 cases for 46.9%, and the time elapsed between infection and the appearance of sepsis was 0 to 3 hours in 43 cases. There was an association between septic shock and the volume dose administered at 60ml / kg of body weight. The stay that predominated in the series was between 3 and 7 days in 41 patients. Conclusions: A clinical characterization of pediatric patients with sepsis admitted to the intensive care unit at Morón hospital was carried out, which is classified within second-level care hospitals, for 4 years, among the main variables is the predominance of the sepsis stage and the relationship between septic shock and the volume dose at 60ml / kg of body weight.